2022
DOI: 10.3389/fnut.2021.724497
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Body Adiposity and Alcohol Consumption on Serum Uric Acid: A Quantile Regression Analysis Based on the China National Health Survey

Abstract: Adiposity and alcohol consumption are reported to be associated with a higher level of serum uric acid (SUA), but whether their effect differs on SUA percentile distribution is still unclear. In this study, we aimed to investigate how alcohol intake and body fat percentage (%BF) integrated with body mass index (BMI) influence the distribution of SUA in Chinese adults. Data from the China National Health Survey (CNHS) which included adults from 10 provinces of China were used (n = 31,746, aged 20–80 years, 40% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…In this population-based cohort study with 9.94-year follow-up, the HLS, a composite healthy lifestyle measure of smoking, alcohol consumption, physical activity, diet, and body composition, was inversely associated with the risk of T2DM, and such association was partially Table 3 Adjusted HR for association between baseline SUA and T2DM Model 1: adjusted for age, sex, healthy lifestyle scores (continuous), family history of diabetes, family history of hypertension, prevalence of hypertension, use of antihypertensive medication, and use of lipid-lowing medication Model 2: Model1 + TG (mmol/L), HDL-C (mmol/L), and FPG (mmol/L) # sex-specific quartile of baseline SUA:74-, 312-, 363-, 423-768 µmol/L for male, 74-, 231-, 271-, 317-859 µmol/L for female * Hyperuricemia was defined as SUA ≥ 420 µmol/L for men and SUA ≥ 360 µmol/L for women HR, hazard ratio; SUA, serum uric acid; T2DM, type 2 diabetes mellitus; CI, confidence interval; SD, standard deviation There has been preponderant evidence on the impact of individual lifestyle behaviors. For example, there is evidence that SUA is linked to dietary factors [31,32], and adiposity and alcohol consumption are associated with a higher SUA [33]. Mean change in BMI, but not in WC, was statistically significantly associated with change in SUA over a 1-year follow-up in males [34].…”
Section: Discussionmentioning
confidence: 99%
“…In this population-based cohort study with 9.94-year follow-up, the HLS, a composite healthy lifestyle measure of smoking, alcohol consumption, physical activity, diet, and body composition, was inversely associated with the risk of T2DM, and such association was partially Table 3 Adjusted HR for association between baseline SUA and T2DM Model 1: adjusted for age, sex, healthy lifestyle scores (continuous), family history of diabetes, family history of hypertension, prevalence of hypertension, use of antihypertensive medication, and use of lipid-lowing medication Model 2: Model1 + TG (mmol/L), HDL-C (mmol/L), and FPG (mmol/L) # sex-specific quartile of baseline SUA:74-, 312-, 363-, 423-768 µmol/L for male, 74-, 231-, 271-, 317-859 µmol/L for female * Hyperuricemia was defined as SUA ≥ 420 µmol/L for men and SUA ≥ 360 µmol/L for women HR, hazard ratio; SUA, serum uric acid; T2DM, type 2 diabetes mellitus; CI, confidence interval; SD, standard deviation There has been preponderant evidence on the impact of individual lifestyle behaviors. For example, there is evidence that SUA is linked to dietary factors [31,32], and adiposity and alcohol consumption are associated with a higher SUA [33]. Mean change in BMI, but not in WC, was statistically significantly associated with change in SUA over a 1-year follow-up in males [34].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional survey from 2013 to 2014 in southwest China among middle-aged adults also showed a higher hyperuricemia prevalence in men than in women (17.3 vs. 10.0%) ( 26 ). The inconsistence among prevalence may be attributed to the population heterogeneity, disparity on covariates distribution, survey time variation of hyperuricemia as its increasing trend, or geographic difference ( 8 , 9 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Life-style risk factors, such as excess adiposity, alcohol consumption, cigarette smoking, and sedentary behavior, were found to be associated with hyperuricemia ( 8 , 9 , 11 , 34 38 ). Mendelian randomization studies have demonstrated the causal associations among excess adiposity and alcohol consumption with elevated SUA ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between adiposity and SUA has been demonstrated by substantial evidence (14)(15)(16). Our previous analysis also indicated that adiposity is related to SUA and hyperuricemia (6,17). Given that body mass index (BMI) is not able to distinguish adiposity between fat-free mass (FFM) and fat mass (FM), the current study uses BMI, fat mass index (FMI), and fatfree mass index (FFMI) as the measurement of body composition.…”
Section: Introductionmentioning
confidence: 92%